Unintentional injuries and risk behaviours of internal migrant children in southern China: A cross‐sectional study. (16th September 2021) - Fei, Gaoqiang; Li, Xinyu; Yang, Yaming; Wei, Pingmin; Stallones, Lorann; Xiang, Henry; Zhang, Xujun
Abstract: The purpose of this study was to estimate the prevalence of unintentional injuries and to identify factors mediating the risk of unintentional injuries among internal migrant children in southern China using self‐reported data collected between April 2016 and March 2017. Logistic regression models were used to identify significant risk factors for unintentional injuries among the internal migrant children. The prevalence of self‐reported unintentional injuries among internal migrant children in this study was 19.15%. Internal migrant children exhibiting antisocial (antisocial behaviour vs. no behaviour problems, OR = 2.162, 95% CI: 1.194–3.915, p  = .011) and neurotic behaviours (neurotic behaviour vs. no behaviour problems, OR = 2.064, 95% CI: 1.098–3.880, p  = .024) were more likely to report unintentional injuries. There was a positive correlation between the number of risk behaviours and the prevalence of unintentional injuries among non‐migrant and internal migrant children. Children's behavioural problems were closely related to unintentional injuries and may be useful as predictors of unintentional injuries in children.